Education and Democratic Transformation An Analytical Study of Some Theoretical Approaches (Journal of the College of Basic Education, 2026)
In this research paper, the researchers sought to explore the relationship between secondary education and the democratic transition process, based on a basic hypothesis emphasized by the most common theoretical approaches: the quality of secondary education is an important variable in building democratic values ​​and principles among students, thereby consolidating a culture of democracy in society. Therefore, the main question of the current research paper was: What is the relationship between education and democratic transition, according to the theoretical literature? The aim of the research was to describe and analyze the theoretical approaches to the relationship between education and democratic transition. The researchers defined the concepts of "education" and "democratic transition." They presented the three most common approaches to discussing the relationship between education and democratic transition: "modernization," "transitional," and "structural approaches." They also presented the most important criticisms directed at them. The research paper reached a set of results. It was divided into two sections. The first included "Research Elements," which addressed the research problem, its importance, and its objective. The second section also defined the concepts of "education" and "democratic transition." Finally, it concluded with a conclusion.